COKEK SEBAGAI PENGARUH PENETRATION PASIPIQUE ETNIS TIONGHOA DI BETAWI - Nurul Rohmawati (Institut Seni Budaya Indonesia (ISBI) Bandung, 2018)
ABSTRACT Tionghoa ethnic becomes part of the formation of the Betawi community which also plays a role in the assimilation of Betawi culture. Cokek art is one of the results of the assimilation which is also part of the Betawi culture. The forms and functions of Cokek art that change from time to time are also influenced by the policies of the Jakarta City Government and the people who oppose them.The community does not only need to know about the changes in the shape and function of Cokek art from time to time, but also need to know how the cokek becomes part of the Betawi culture. This is related to the way in which new elements of culture enter the Betawi society from the standpoint of social anthropology.Based on the use of descriptive qualitative methods with interpretive points of view in the study, it is known that cokek is a penetration influence of Tionghoa ethnic pasipique in Betawi. Key words: Cokek, Penetration Pasipique, Tionghoa Ethnic, Betawi. ABSTRAK Etnis Tionghoa turut menjadi bagian dari pembentukan masyarakat Betawi yang juga berperan dalam asimilasi kebudayaan Betawi itu sendiri. Kesenian cokek merupakan salah satu hasil asimilasi tersebut yang juga menjadi bagian dari kebudayaan Betawi. Adapun bentuk dan fungsi kesenian Cokek yang berubah dari waktu ke waktu turut dipengaruhi oleh kebijakan pemerintah Kota Jakarta dan masyarakat penyanggahnya.Masyarakat tak hanya perlu mengetahui tentang perubahan bentuk dan fungsi kesenian Cokek dari waktu ke waktu, tetapi juga perlu diketahui cara Cokek menjadi bagian dari kebudayaan Betawi. Hal ini berhubungan dengan cara masuknya unsur kebudayaan baru dalam masyarakat Betawi dari sudut pandang antropologi sosial.Berdasarkan pemanfaatan metode kualitatif deskriptif dengan sudut pandang interpretif dalam penelitian, diketahui bahwa Cokek sebagai pengaruh penetration pasipique etnis Tionghoa di Betawi. Kata Kunci: Cokek, Penetration Pasipique, Etnis Tionghoa, Betawi.